Long Non-Coding RNA MEG3 Modifies Cell-Cycle, Migration, Invasion, and Proliferation Through AKAP12 by Sponging miR-29c in Meningioma Cells - Ding, Chenyu; Yi, Xuehan; Xu, Jiaheng; Huang, Zhenhua; Bu, Xingyao; Wang, Desheng; Ge, Hongliang; Zhang, Gaoqi; Gu, Jianjun; Kang, Dezhi; Wu, Xiyue (Frontiers in Oncology, 2020)
Meningioma (MEN) is a common central nervous system disease. Accumulating evidence indicated that long non-coding RNA maternally expressed gene 3 (MEG3) participated in the progression of MEN. However, the potential mechanisms of MEG3 in altering the aggressive phenotypes of MEN need further exploration. Levels of MEG3, microRNA (miR)-29c, and A-kinase anchor protein 12 (AKAP12) were determined using quantitative real-time Polymerase Chain Reaction (qRT-PCR) assay. Dual-luciferase reporter and RNA immunoprecipitation (RIP) assays were performed to verify the relationship between miR-29c and MEG3 or AKAP12. Besides, the protein level of AKAP12 was detected by western blot. Moreover, cell-cycle arrest, migration, invasion and proliferation were assessed by flow cytometry, wound healing, transwell assays and CCK-8 assay, respectively. Levels of MEG3 and AKAP12 were downregulated, while miR-29c was effectively increased in MEN tissues and cell line. Mechanically, MEG3 was a sponge of miR-29c to regulate the expression of AKAP12. Functionally, increase of MEG3 diminished cell-cycle, migration, invasion and proliferation in MEN cells, and reintroduction of miR-29c could eliminate these effects. In addition, AKAP12 depletion overturned the inhibitory effects of miR-29c absence on cell-cycle, migration, invasion and proliferation in vitro. Also, AKAP12 was co-regulated by MEG3/miR-29c axis. MEG3 mediated the aggressive behaviors of MEN cells via miR-29c/AKAP12 axis, supporting that MEG3 served as a promising biomarker for the diagnosis and treatment of human MEN.